Enhancing Auditor Independence in Developing Countries in the Context of Globalization – Evidence from Vietnam - Duc, Le Doan Minh (Journal of Accounting, Business and Finance Research, 2021)
Globalization brings many opportunities and challenges for developing countries. So, does globalization create a motivation to improve the auditing profession’s ethics? Independence is one of the most important components of professional auditing ethics and must be maintained throughout the audit process. This article takes a new approach to auditor independence based on globalization in Vietnam and delivers a full insight into identifying factors that enhance auditor independence in the international integration process. A mixed approach to this study is taken based on experimental methodology. This article uses the archival research and group discussion methods to analyze and assess the research problems. Group discussions were conducted with experts and 280 directors, auditors, and auditor assistants who work in 70 auditing firms were surveyed. The results showed that globalization supports auditors, audit firms, and professional association to improve auditor independence. Factors that particularly enhance auditor independence driven by international integration are knowledge, technology, competition, management, and monitoring. Based on the results of the study, it is recommended that auditor independence should be improved in the context of Vietnam due to the country being integrated internationally.